Building your marriage - Rainey, Dennis, 1948- (Bangalore. Family Life, a division of India campus crusade for Christ., 2000)
"This 7-session small group study is designed to bring husbands and wives closer to each other, closer to God--and closer to the other couples. You will study God's Word, share in your challenges and successes, and build a marriage that will last"--Cover p. [4].
Keywords: Marriage -- Religious aspects -- Christianity; Marriage -- Handbooks, manuals, etc